Explaining E-Wallet Adoption Among SMEs in Indonesia: An Extended Protection Motivation Theory Approach - Muhammad Awaluddin (Journal of Digital Business and Global Economy, 2025)
This study explores the determinants of e-wallet adoption among small and medium enterprises (SMEs) in the Indonesian food and beverage sector by applying Protection Motivation Theory, extended with trust and privacy concern. A cross-sectional survey of 400 SME owners and managers was conducted using a semantic differential scale, and the data were analyzed with structural equation modeling. The measurement model demonstrated strong reliability and validity, while the structural model provided robust explanatory power. The results revealed that perceived vulnerability, perceived severity, response efficacy, and self-efficacy positively influenced intention to adopt e-wallets, whereas response cost and privacy concern had negative effects. Trust played a dual role, directly enhancing both intention and actual use, and moderating the relationship between intention and behavior. Intention was also confirmed as the key mediator linking cognitive appraisals to adoption behavior. Overall, the model explained 62% of the variance in intention and 71% in actual use, demonstrating its strong predictive capacity. These findings highlight the importance of trust, efficacy beliefs, and cost perceptions in shaping digital payment adoption, offering both theoretical insights and practical guidance for fintech providers and policymakers in emerging markets